Left-wing populism : the politics of the people - Agustín, Óscar García (Emerald points., 2020)
In the aftermath of the economic crisis, left-wing parties and leaders began to consider themselves populists or were labelled as such in media and public discourse. This trend can be witnessed in instances such as Syriza in Greece, Podemos in Spain, France Insoumise in France, DiEM25 at the European level and even Corbyinism in the UK. However, the problem still remains as to how we define left-wing populism in contemporary Europe as well as the main characteristics. This book conceptualizes left-wing populism as a combination of the populist impetus of expanding representation, through the appeal to "the people" against "the elites" and the agenda of the left to promote equality and social justice. This study undertakes an in-depth exploration into the concepts of sovereignty, class identity and "the people". Moreover, this book also discusses the institutional dimension of left-wing populism, in dialogue with republicanism and the international sphere, reflected in the debate between sovereignism and transnationalism. The result is an open conceptualization of left-wing populism in which populist parties acquire a hybrid form and incorporate different traditions and influences such as socialism, populism and republicanism in order to reach a social majority and expand democracy. This recent phenomenon of left-wing populism has showed potential to re-define the left-project, but also demonstrates its shortcomings regarding the scope of the political change and its capacity to make politics in a different manner, by and for the people. This invaluable text will prove an essential read for those in the fields of political theory and contemporary political studies.